35th Aerospace Sciences Meeting and Exhibit 1997
DOI: 10.2514/6.1997-1
|View full text |Cite
|
Sign up to set email alerts
|

Conflict probability estimation for free flight

Abstract: The safety and e ciency of free ight will bene t from automated con ict prediction and resolution advisories. Con ict prediction is based on trajectory prediction and is less certain the farther in advance the prediction, however. An estimate is therefore needed of the probability that a con ict will occur, given a pair of predicted trajectories and their levels of uncertainty. This paper presents a method to estimate that con ict probability. The trajectory prediction errors are modeled as normally distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
160
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(162 citation statements)
references
References 1 publication
0
160
0
2
Order By: Relevance
“…A similar class of models are geometric conflict models (e.g., Paielli and Erzberger 1997, 1999, Irving 2002. In these models, the velocities of the airplanes are fixed as before, but their initial positions (in three dimensions) are random.…”
Section: Collision Prediction Modelsmentioning
confidence: 99%
“…A similar class of models are geometric conflict models (e.g., Paielli and Erzberger 1997, 1999, Irving 2002. In these models, the velocities of the airplanes are fixed as before, but their initial positions (in three dimensions) are random.…”
Section: Collision Prediction Modelsmentioning
confidence: 99%
“…However, since the prediction error can be modeled as the sum of a large number of independent random perturbations in disjoint time intervals, it is expected to be Gaussian. This hypothesis was indeed verified by empirical data in [2], which also suggested that the uncertainty can be decomposed into two components: an along track component whose variance grows with time, and a cross track component whose variance remains roughly constant. Based on this model, a number of methods have been proposed to predict the probability of conflict (PC) for aircraft pairs over horizons of the order of 20 minutes.…”
Section: Introductionmentioning
confidence: 50%
“…A conflict occurs if the intruder enters the protected zone of radius 5 nmi around aircraft 1 or vice versa. (2) where C = diag(o,,c,). c,,u, model the variance growth rate in the along track and cross track component respectively (no > oc typically).…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations